Papillary pineocytoma in child: a case report - Marcol, Wiesław; Kotulska, Katarzyna; Grajkowska, Wiesława; Gołka, Dariusz; Właszczuk, Paweł; Drogosiewicz, Monika; Mandera, Marek; Lewin-Kowalik, Joanna; Roszkowski, Marcin (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2007)
BACKGROUND: Papillary pineocytoma is an extremely rare tumor usually with a poor outcome. CASE REPORT: We report a case of a 10-year-old-girl with pineal gland tumor and obstructive hydrocephalus diagnosed using MRI. The child was successful treated by insertion of a ventriculoperitoneal shunt and consecutive tumor resection by supracerebellar-infratentorial approach. Histopathological examination showed a papillary structure of the pineocytoma. As such, tumors are considered to be aggressive the child was subjected to radio- and chemotherapy. CONCLUSION: At six year follow-up after surgery, the patient is symptom-free and the MRI shows no tumor recurrence.
Keywords: ženské pohlaví; Child; Female; Humans; lidé; Pineal Gland; nádory mozku; pinealom; Brain Neoplasms; dítě; epifýza mozková; Pinealoma